Marketing Mix Stategy at Mamba`ul Ma`arif Islamic Boarding School Jombang - Abdul Fattah Wahab; Amrozi Khamidi; Dewie Trie Wijayati Wardoyo (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Currently, competition in education is unavoidable, and many educational institutions are then abandoned by society. The managerial ability to understand the marketing of educational services is a prerequisite in maintaining its existence and increasing the educational institutions. The marketing concept, which was initially only known and applied in profit-oriented organizations, can also be used in non-profit organizations, including Pesantren. Pesantren during the three decades (1997-1998) could be classified into two major types: first, the old or classical type, which is learning about classical Islamic texts; second the new type, namely establishing several schools and madrasah. Pesantren Mamba`ul Ma`arif Denanyar Jombang is included in a new type of Islamic Boarding School. This research attempts to analyze the managerial strategy that`s used in the Pesantren. This research allows qualitative and data sources will be narrated by a descriptive method.